Characteristics of Morbidity and Choice of Health Care Facilities in Nepal - Thapa, Arjun Kumar; Adhikari, Shiva Raj (Journal of Advanced Academic Research, 2017)
In aftermath of People’s Movement 2008, the Government of Nepal promulgated health as a component of basic human rights. But Nepalese health consumers can seek health care services in government primary health facilities, hospitals, private clinics or do self–medication. The study intends to describe the characteristics of morbidity and factors associated in choosing particular type of health facility. For data, the study depends on a nationally representative rich cross sectional household survey data (Nepal Living Standard Survey, 2010/11) of Nepal. The findings of the study show that around one fifth of the total population reported acute illness while near about 10 percent is facing chronic illness. Around 30 percent of people reporting acute illness do not seek any health care services. Most of the rural people and poor population seek health care services in government primary health care facilities and private pharmacies. People belonging to low income quintiles are likely to seek health care services in government primary facilities. Similarly people residing in mountain & hill are likely to utilize services of government primary facilities. The study shows that urbanites are more likely to seek services in hospitals and private clinics. Therefore a homogeneous health care service production and delivery cannot address the country wide demand of health care services.